1990
DOI: 10.1111/j.1745-6584.1990.tb02230.x
|View full text |Cite
|
Sign up to set email alerts
|

Well‐Purging Criteria for Sampling Purgeable Organic Compounds

Abstract: Ground‐water‐sampling protocols generally recommend that a well be purged prior to sampling. This recommendation is based on the assumption that the water quality of the water standing in the casing is not the same as that in the aquifer. Three criteria that have been used to determine when a well has been purged sufficiently to yield “representative” water‐quality samples are (1) flushing an arbitrary number of casing volumes, usually a minimum of three, (2) flushing the well until field water‐quality charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 8 publications
3
32
0
Order By: Relevance
“…The six pumps considered perform purging and sampling functions without significant loss of volatile constituents from the water samples. This statement is supported by numerous reports of relevant research in the scientific literature Ho 1983;Unwin 1984;Barcelona et al 1984Stolzenburg and Nichols 1985;Garske and Schock 1986;Muska et al 1986;Pearsall and Eckhardt 1987;Imbrigiotta et al 1988;Panko and Barth 1988;Pohlmann and Hess 1988;Schalla et al 1988b; Unwin and Maltby 1988;Gibs and Imbrigiotta 1990;Gass et al 1991;Gibs et al 1993;Knobel and Mann 1993;Parker et al 1993).…”
Section: 2mentioning
confidence: 49%
“…The six pumps considered perform purging and sampling functions without significant loss of volatile constituents from the water samples. This statement is supported by numerous reports of relevant research in the scientific literature Ho 1983;Unwin 1984;Barcelona et al 1984Stolzenburg and Nichols 1985;Garske and Schock 1986;Muska et al 1986;Pearsall and Eckhardt 1987;Imbrigiotta et al 1988;Panko and Barth 1988;Pohlmann and Hess 1988;Schalla et al 1988b; Unwin and Maltby 1988;Gibs and Imbrigiotta 1990;Gass et al 1991;Gibs et al 1993;Knobel and Mann 1993;Parker et al 1993).…”
Section: 2mentioning
confidence: 49%
“…Many studies have identified how anomalous or otherwise unrepresentative results may be generated from traditional purge and sampling techniques (e.g. Robbins, 1989, Gibs andImbrigiotta, 1990;Reilly and Gibs, 1993;Conant et al, 1995;Church and Granato, 1996, Martin-Hayden and Robbins, 1997, Reilly and LeBlanc, 1998, Hutchins and Acree, 2000, Elci, et al, 2001. Common situations shown by these and other studies have caused investigators to question what traditional purge-and-sample ground water monitoring results represent.…”
Section: Introductionmentioning
confidence: 99%
“…Sampling technique (pump type, flow rate, discharge tube materials, purge volume, etc.) has also been shown to influence the resultant samples and their representativeness of formation water, particularly for volatile organic compounds (Barcelona et al 1984; Keely and Boateng 1987; Robin and Gillham 1987; Gibs and Imbrigiotta 1990; Barcelona et al 1994; Puls and Barcelona 1996; Herzog et al 1998). Current geochemical sampling protocols call for the purging of the well prior to sample collection to eliminate the fractional contribution of the original borehole contents to the pump discharge (Puls and Barcelona 1996; Nielsen 2007).…”
Section: Introductionmentioning
confidence: 99%